Diagnosis and management of the patient with contaminated illicit drug poisoning - Pino, Richard M.; McGrew, Patrick R. (Frontiers in Anesthesiology, 2023)
The diagnosis and management of poisoning is essential in critical care medicine. Traditionally, these conditions fall under the category of toxidromes that are the signs and symptoms associated with a particular class of poisons. However, there has been a steady increase in designer drugs and contaminants of recreational drugs themselves. Examples of adulterants in cocaine include the local anesthetic benzocaine and the anti-parasitic levamisole. This paper presents the clinical signs, laboratory findings, and treatment of patients who have been exposed to these substances.Admissions to the ICU related to substance abuse is, unfortunately, a common global issue. A recent study revealed that substance abuse was responsible for one quarter of ICU admissions and 23% of total charges (1). Illicit drug use was associated with 13% of these patients (1). Identification of the illicit drug on clinical presentation is often difficult. These substances often fall into multiple categories of toxidromes, the signs and symptoms associated with a particular class of poisons (2). Polysubstance abuse is common. There has been the increasing use of "adulterants" that are legal substances which are added to these illicit drugs. This process, called "cutting," is to either further enhance their effects or expand volume, both of which enhance the drug dealers' profits (3,4). Laboratory tests can confirm the most common illicit substances but often will not identify altered forms (5). Our experience in a trauma center encompasses patients with substance abuse issues, but we had sparse knowledge of contaminants before caring for the patient in the clinical example below. In this paper we present examples illicit drug contaminants, a little-known subject for critical care physicians.